Effect of Kangaroo Mother Care on Weight Gain in Preterm Infants at Tertiary Care Hospital - Rafiq, Ayesha; Waqar, Talal; Kaleem, Ammara; Riaz, Mayda; Waqqas, Arouj (Pakistan Armed Forces Medical Journal, 2025)
Objective: To ascertain effect of Kangaroo mother care (KMC) on weight gain in preterm infants at a tertiary care hospital. Study Design: Quasi-experimental study Place and Duration of Study: Neonatal unit of Combined Military Hospital, Lahore, Pakistan, from Oct 2022 to Mar 2023. Methodology: Neonates were included in the study after obtaining approval from the institutional review board and consent from parents in both the Kangaroo Mother Care (KMC) Group (n=60) and the Control Group (n=60). Infants born between 30 and 35 weeks of gestational age and weighing between 1000 g and 2000 g were selected for the study and divided into two groups using a simple random approach. Results: Out of the 132 newborns, 120(90.90%) were selected, with 60(50%) in each group. The KMC Group demonstrated a higher average weight gain from day 7 to day 14 (16.429±2.64gm g) compared to the Control Group (10.429±2.62gm g) with statistical significance (p<0.0001). The increase in weight each day did not show a statistically significant difference between the two groups (p>0.05). Subgroup evaluations of 41 infants (68.3%) in the intervention group showed that they exclusively breastfed at discharge, compared to only 23 infants (38.3%) in the Control Group who initiated breastfeeding at discharge. Conclusion: In comparison to conventional mother care, Kangaroo mother care is a potent tool for improved weight gain in preterm babies in LMIC, along with its beneficial effect on establishing exclusive mother feed at discharge.